UNVEILING A RARE CASE OF KIKUCHI-FUJIMOTO IN SINDH, PAKISTAN - Bano , Saira; Jawed, Inshal; Fatima , Fasiha Bakhtawar; Alam , Mohammad Omer; Feroze , Ahsan (Journal of Ayub Medical College Abbottabad, 2024)
Kikuchi-Fujimoto disease (KFD) commonly manifests with symptoms of fever, tender cervical adenopathy, and systemic symptoms like night sweats, rashes, headache, weight loss, nausea, vomiting, and sore throat. In this case study, a 27-year-old patient’s main complaints included fever, neck oedema, and weight loss that started one month ago. Following preliminary inquiries, ultrasonography, and CT scans, a multidisciplinary team has been overseeing the case. After a biopsy of axillary and cervical lymph nodes, it has been diagnosed as a case of Kikuchi-Fujimoto disease overlapping with Systemic Lupus Erythematous. Symptomatic and specific treatment started which showed improvement in 4 weeks. The treatment is symptomatic because of the benign characteristic and typical resolution within several weeks to months. The prognosis is usually excellent without an increased risk of malignancy or mortality.